Declining Service Labor Rates for Total Hip and Total Knee Arthroplasty in Medicare Patients - John M. Dundon, MD, FAAOS; Nicholas Brown, BS; Jennifer Escobar, BS, RN; Paul M. Lombardi, MD, FAAOS (Arthroplasty Today)
Background: Total hip (THA) and knee arthroplasty (TKA) are highly successful surgeries, but reimbursement for these procedures has decreased due to relative value unit scale devaluation and Medicare cuts. The shift to outpatient joint replacements has increased workload for orthopaedic surgeons and office staff while saving Medicare costs. This study evaluates 3 groups of orthopaedic surgeons to determine their hourly rate for Medicare total joints. Methods: We categorized 3 groups of orthopaedic surgeons by operative time and efficiency to assess hourly rates. Group 1 performs 2-3 cases daily, group 2 performs 4-5 cases, and group 3 performs 10+ cases. We evaluated total operative time based on historical data and Centers for Medicare & Medicaid Services guidelines for preoperative and postoperative time. Results: For group 1, average times for THA and TKA were 400 minutes ($188.89/hour) and 408.5 minutes ($184.92/hour). Group 2's times and hourly rates for THA and TKA were 401.5 minutes ($188.18/hour) and 404 minutes ($190.68/hour). Group 3 had total times of 300.5 minutes ($251.50/hour) for THA and 300.25 minutes ($256.57/hour) for TKA. Conclusions: With decreasing actual rates and even further decline in inflation adjusted reimbursement and increasing practice costs, some surgeons may have to consider discontinuation of or minimizing TKA and THA in Medicare patients to maintain financial viability.